THE INTONATION STRUCTURE OF ENGLISH: A COMPREHENSIVE ANALYSIS - Ubaydullayeva Sadoqat Sobirjon Qizi; Abduraimova Shabnam Zokirjon Qizi; Eshbo’riyeva Husnora Azamat Qizi (TADQIQOTLAR, 2025)
Abstract Intonation, the variation in pitch during speech, is a fundamental feature of English that conveys grammatical structure, emotional nuance, and discourse dynamics. This study examines the components, patterns, and functions of intonation in English across various sentence types and contexts. Through corpus analysis, phonetic transcription, and contextual evaluation, we illustrate how intonation shapes meaning. The findings highlight intonation’s critical role in effective communication, with implications for linguistic research, language teaching, and cross-cultural interactions.